Re-Os molybdenite and LA-ICPMS-MC U-Pb zircon geochronology for the Milpillas porphyry copper deposit: insights for the timing of mineralization in the Cananea District, Sonora, Mexico - Víctor A. Valencia; Benito Noguez-Alcántara; Fernando Barra; Joaquín Ruiz; George Gehrels; Francisco Quintanar; Martín Valencia-Moreno (Revista Mexicana de Ciencias Geológicas)
New geochronological data presented here improves the understanding of the temporal evolution of the Cananea Mining District, and particularly of the Milpillas porphyry copper deposit (northeastern Sonora, Mexico). Uranium-lead zircon analyses, using laser ablation ICP-MS multi-collector, from the quartz monzonite porphyry unit that host the mineralization at the Milpillas deposit, yielded a crystallization age of 63.9 ± 1.3 Ma (2-sigma). Re-Os molybdenite ages from two drill core samples from more than 500 m depth yielded an identical age of 63.1 ± 0.4 Ma (2-sigma), suggesting a restricted period of mineralization. These ages indicate that the Milpillas deposit is the oldest Laramide porphyry copper deposit recognized so far in the Cananea District. Our new Re-Os data in addition to previous Re-Os data, suggest that mineralization within the district, occurred within a ~4 m.y. period in three discrete pulses at ~59 Ma, ~61 Ma and ~63 Ma. This is in contrast to the previous model in which mineralization at the Cananea District was the result of a continuous hydrothermal system that started at ~62 Ma and ended at ~52 Ma.